2012
DOI: 10.1017/s2078633612000082
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and bottleneck analysis of Konkan Kanyal goats

Abstract: Konkan Kanyal goats are medium-sized animals reared for meat purpose. They are predominantly black in colour with white markings in a specific pattern and are found in the Kudal, Sawantwadi, Dodamarg, Malvan and Vengurle Talukas of Sindhudurg district of Konkan region of Maharashtra state. The mean body weight ranges from 30 kg in adult females to 35 kg in males. The age at first kidding, kidding interval and twinning of these goats is 546 days, 240 days and 35 percent respectively. The average daily milk yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The allelic polymorphism ranged between 4 (ETH10, ILSTS008) and 17 (BM64444) with a mean number of alleles of 10.14±0.83. The mean observed number of allele recorded in this study was higher than the values reported in Barbari and Kanni Adu goats [5,12] and comparable to the value of 10.20 reported for Konkan Kanyal goats [13]. The high allelic diversity observed is probably due to no selection pressure and choice of samples based on random sampling.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The allelic polymorphism ranged between 4 (ETH10, ILSTS008) and 17 (BM64444) with a mean number of alleles of 10.14±0.83. The mean observed number of allele recorded in this study was higher than the values reported in Barbari and Kanni Adu goats [5,12] and comparable to the value of 10.20 reported for Konkan Kanyal goats [13]. The high allelic diversity observed is probably due to no selection pressure and choice of samples based on random sampling.…”
Section: Resultssupporting
confidence: 61%
“…In general, few studies have reported on the possible occurrence of the genetic bottleneck based on microsatellite data, viz., Dexter, Bargur and African cattle breeds and Valais Blackneck goat [19][20][21][22]. Earlier studies on different Indian and Iranian goat breeds did not reveal any indication of recent occurrence of the genetic bottleneck [1,5,12,13,[23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Matrix of NEI's (1978) showed that all of the studied loci were highly informative, indicating high polymorphism across the loci, thus suggesting suitability of these markers for the study of genetic diversity in buffalos. Suitability of these markers was further supported by the fact that the number of alleles for each marker was higher than the minimum number of alleles (four) recommended for microsatellite markers to be used in the estimation of genetic distance in order to reduce the standard error (MISHRA et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In the present investigation, the markers used are neutral and are widely distributed in the genome, their chromosomal locations are given somewhere else (Verma et al, 2007a). 2010), Changthangi (Mishra et al, 2010) and Konkan Kanyal (Mishra et al, 2012). of alleles; Ne, effective no.…”
Section: Microsatellite Markersmentioning
confidence: 99%